On Model Representations of Non-Selfadjoint Operators with Infinitely Dimensional Imaginary Component - Hatamleh, R.; Zolotarev, V.A. (Журнал математической физики, анализа, геометрии, 2015)
For an entirely non-selfadjoint operator with spectrum at zero, the imaginary component of which has an absolutely continuous spectrum (not necessarily dissipative and having lacunas in the spectrum), triangular and functional models are constructed. Для вполне несамосопряженных операторов со спектром в нуле, мнимая компонента которых имеет абсолютно непрерывный спектр (не обязательно диссипативна и может иметь лакуны в спектре), построены треугольная и функциональная модели. Для цілком несамоспряжених операторів зі спектром в нулі, уявна компонента яких має абсолготно неперервний спектр (не обов'язково дисипативна та може мати лакуни в спектрі), побудовані трикутна та функціональна моделі.